PENGARUH KEAHUAN, PENGETAHUAN, SIKAP DAN ETIKA TERHADAP PROFESIONALISME DOSEN AKUNTANSI PERGURUAN TINGGI SWASTA DI SURAKARTA - Hermawati Pramesti; Dyah Ayu Putri Palupi (Fakultas Bisnis UKDW, 2007)
This research aim to for research of influence skill, knowledge, attitude, and ethics to professionalism of accounting lecturer of College Private sector in Swakorta Hipotesis Proposed by researcher thot skill, knowledge, attitude, and the ethics hwe positive influence in porsial od simultan to professionalism of rccotmting lecturer of College Private Sector in Surakarta Researcher use primory data with population of all accowtting students of College Privote Sector Majors accounting in Surakmta. Sampel use method of Purposive random Sampling, sa that be got 84 from 92 respondm.Technic analyse used is tested of validity And Reliabtly, tested classic asumtion, t test And F test by using SPSS Yersion 14.0. Result from this resemch is lrypothesis exanination indicate thd F test biger ttan F tables so conclusion is vwiable skill, btowledge, dtitude and ethics hwe inJluence together to Profesionalisme accounting lecturer af College of Private secto! in Surakarta. T test bigget than t tables so that conclusion is variable skill, ktowledge, attitude, and theethics have inJluence in parsial to Profesionalisme acoounting lectttre 9f lollege of Plivale sector in SurQkarta- :Keywords: Skill, Knowledge, Attitude, Ethics.